Clozapine Augments Delta, Theta, and Right Frontal EEG Alpha Power in Schizophrenic Patients. (10th May 2012) - MacCrimmon, D.; Brunet, D.; Criollo, M.; Galin, H.; Lawson, J. S.
Abstract : Objective . To explore the Quantitative EEG (QEEG) effects of established clozapine therapy regimes compared to those of previous ineffective antipsychotic regimes among 64 chronic (DSM-IV) schizophrenic patients. Methods . Data from 20 EEG channels referenced to linked ears were collected before and during maintenance clozapine therapy (mean duration 1.4 years). Absolute power was calculated in six frequency bands: delta (0.4–3.6 Hz), theta (4.2–7.8 Hz), alpha (8.2–11.8 Hz), beta1 (12.2–15.8 Hz), beta2 (16.2–19.8 Hz), and beta3 (20.2–23.8 Hz). Results . Clozapine augments power globally in the delta and theta bands, but this effect is more pronounced over frontal areas. Beta3 power was reduced. Alpha showed a frontal increase, more pronounced in the right, coupled with a posterior decrease with no net change in overall power. Conclusion . The demonstration of a significant clozapine-induced alpha topographic shift frontally and to the right is a novel discovery that may serve to encourage further investigations of subcortical structures in attempts to better understand the diverse aetiologies and optimal treatments of the schizophrenias.